Study on the Identification of the Professional Integration Needs - Maramureș County - Berlingher, Vasile (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
After 1989 the North West part of the country has undergone a major restructuring process of the mining field with a huge impact on the situation of the human resource of the area and many economic and social problems. The legislation on the restoring and rehabilitating the mining perimeters and the one on social protection was oriented towards the destruction of mining. Thus, the restructuring of the majority of the staff in this sector has brought about the worsening of the economic and social situation of the population in the area. No account was taken of the fact that 70% of the products manufactured in the European Union and 30 million jobs in different industries depend on the raw mining material. The funds assigned for closing mines, for measures of regional development through creating new jobs were wasted. If they had been efficiently oriented towards re-technologizing the mining sector, its importance could have been highlighted as well as the essential role and importance of minerals in the increase of the quality of life. It was not meant to be; in 1998 the area was declared disfavoured area, with an unemployment rate above the national average.